Preparation of nanocrystalline ferroelectric CaBi2TaO9 by citrate gel method - Gaikwad, S. P.; Pasricha, R; Ravi, V (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
A gel was formed when an aqueous solution of CaCl2, BiCl3, TaF5 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 600degreesC yielded the nano-crystallites of ternary oxide, CaBi2Ta2O9 (CBT) as confirmed by X-ray diffraction study (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). Ferroelectric hysteresis loop parameters such as remnant polarization (P-r) and coercive field (E-C) are also determined. TEM investigations revealed that the average particle size of the polycrystalline powder is 40 nm. The room temperature dielectric constant was found to be 90. (C) 2004 Elsevier B.V All rights reserved.
Keywords: Bismuth; diffraction; Electron microscopy